2020
DOI: 10.1007/s12551-020-00675-8
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous fluid-like movements of chromatin and their implications to transcription

Abstract: Eukaryotic chromatin is a complex of genome DNA and associated proteins, and its structure and dynamics play a crucial role in regulating DNA functions. Chromatin takes rather irregular structures in the nucleus and exhibits heterogeneous sub-diffusive movements as polymers fluctuating in a fluid state. Using genome-wide single-nucleosome tracking data, heterogeneity of movements was statistically analyzed, which categorized chromatin into two types: slow chromatin that moves under structurally constrained env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 72 publications
(93 reference statements)
1
21
0
Order By: Relevance
“…Rapid local chromatin movements has also been obtained by combining confocal microscopy of fluorescently labeled bulk histones or DNA binding fluorophores with displacement correlation analysis [ 182 , 186 ]. Finally, statistical analyses [ 187 , 188 ] of genome-wide single nucleosome tracking data [ 133 ] have demonstrated that the genomic nucleosomes show fluid-like behavior at the 300-nm length scale. Taken together, these studies demonstrate that chromatin locally is not a rigid solid and has some dynamic features that are suggestive of liquid-like properties.…”
Section: Solid and Liquid States Of Chromatin In The Nucleusmentioning
confidence: 99%
“…Rapid local chromatin movements has also been obtained by combining confocal microscopy of fluorescently labeled bulk histones or DNA binding fluorophores with displacement correlation analysis [ 182 , 186 ]. Finally, statistical analyses [ 187 , 188 ] of genome-wide single nucleosome tracking data [ 133 ] have demonstrated that the genomic nucleosomes show fluid-like behavior at the 300-nm length scale. Taken together, these studies demonstrate that chromatin locally is not a rigid solid and has some dynamic features that are suggestive of liquid-like properties.…”
Section: Solid and Liquid States Of Chromatin In The Nucleusmentioning
confidence: 99%
“…These networks have not only been associated with phase separation events but also with the formation of transient chromatin bridges [ 88 ]. Interestingly, whilst active chromatin regions are usually associated with open and dynamic conformations, recent reports challenge this view by showing that the bridging effect of RNAPII and associated transcription machinery can increase chromatin constraints, reduce chromatin mobility and possibly affect local stiffness [ 89 , 90 ].…”
Section: Contributing Factors To Nuclear Mechanicsmentioning
confidence: 99%
“…Both disruption of nuclear actin polymerisation and MVI force-sensing—through the introduction of an MVI spring mutant that changes its response to force—abrogate RNAPII distribution and have severe consequences for gene expression using RNA-Seq [ 34 ]. The role of MVI in regulating RNAPII clustering also suggests a role for this molecular motor in RNAPII-dependent chromatin bridging and droplet formation [ 89 , 90 ], thus leading to local changes to chromatin mechanics.…”
Section: Contributing Factors To Nuclear Mechanicsmentioning
confidence: 99%
“…Actually, recent efforts to visualize chromatin in cells using cryo-electron tomography (cryo-ET) and related techniques [ 118 , 119 ] are supporting a dynamic fluid-like organization of chromatin [ 120 ] rather than the rigid 30-nm chromatin fiber model based on in vitro chromatin studies that was widely accepted for decades. Comprehensive chromatin models based on an array of biophysical studies propose chromatin to be organized in distinct domains that have irregular fluid-like nucleosome organization [ 121 ].…”
Section: Cenp-a Nucleosome—a Chromatin-embedded Pedestal For the Centmentioning
confidence: 99%